1996
DOI: 10.1111/j.1365-246x.1996.tb04051.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic susceptibility of soil: an evaluation of conflicting theories using a national data set

Abstract: Magnetic susceptibility values for topsoils across England are combined with data for soil type, geochemistry and concentrations of magnetotactic bacteria in order to evaluate different theories for explaining soil magnetism. Strongly magnetic soils in unpolluted areas are found over weakly magnetic substrates and are dominated by ultrafine superparamagnetic grains. Magnetotactic bacteria are present in insufficient concentrations to account for strongly magnetic soils, and crop burning is discounted as a majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
264
1
15

Year Published

1998
1998
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 381 publications
(304 citation statements)
references
References 33 publications
16
264
1
15
Order By: Relevance
“…Thompson and Oldfield, 1986). Numerous studies have demonstrated that magnetic techniques can be successfully used to monitor anthropogenic or geoanthropogenic pollution from surface soils (Dearing et al, 1996b;4 Jordanova et al, 2003;Qiao et al, 2011;Zheng and Zhang, 2008;Zhu et al, 2010), fossil fuel combustion (Heller et al, 1998), coastal areas (Dong et al, 2014;Zhang et al, 2009), urban dust (Bucko et al, 2011;Shilton et al, 2005;Shu et al, 2000;Xie et al, 1999;Zhu et al, 2010) and historical monuments (Schiavon and Zhou, 1996). Zhang et al (2012) show the first example for the use of magnetic measurements in detecting the iron-containing particles in the Shanghai subway system.…”
Section: Introductionmentioning
confidence: 99%
“…Thompson and Oldfield, 1986). Numerous studies have demonstrated that magnetic techniques can be successfully used to monitor anthropogenic or geoanthropogenic pollution from surface soils (Dearing et al, 1996b;4 Jordanova et al, 2003;Qiao et al, 2011;Zheng and Zhang, 2008;Zhu et al, 2010), fossil fuel combustion (Heller et al, 1998), coastal areas (Dong et al, 2014;Zhang et al, 2009), urban dust (Bucko et al, 2011;Shilton et al, 2005;Shu et al, 2000;Xie et al, 1999;Zhu et al, 2010) and historical monuments (Schiavon and Zhou, 1996). Zhang et al (2012) show the first example for the use of magnetic measurements in detecting the iron-containing particles in the Shanghai subway system.…”
Section: Introductionmentioning
confidence: 99%
“…The mapping of magnetic susceptibility is ideal for studies that require large amounts of samples, as of spatial variability, for example (Dearing et al, 1996). Thus, the combined use of this method of indirect analysis with multivariate statistics provides valuable information for the mapping of homogeneous areas with a view to develop strategies for different agricultural systems.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Magnetic methods have been applied in recent years to environmentally related problems, such as the monitoring of soils for contamination [e.g., Dearing et al, 1996], or as a proxy for climatic changes in terrestrial, lacustrine, and marine environments [e.g., Maher and Thompson, 1999;Thompson and Oldfield, 1986;Verosub and Roberts, 1995]. Because magnetic properties are sensitive to the presence of iron oxides in concentrations that are hardly detectable by spectroscopic and X-ray diffraction methods, they have been useful for the study of iron phases in soils [e.g., LeBorgne, 1955;Maher and Taylor, 1988;Mullins, 1977].…”
Section: Introductionmentioning
confidence: 99%